The Effect of Profitability, Leverage and Capital Intensity on Tax Avoidance (Study of Non Cyclicals Consumer Sector Companies Listed on the IDX in 2019-2023) - Akmal, Oktafiana (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
From 2019 to 2023, this study will look at the consumer non-cyclicals sector companies listed on BEI to see how tax avoidance is influenced by profitability, leverage, and capital intensity. In this study, profitability, leverage, and capital intensity are treated as independent variables. To the contrary, tax evasion is the dependent variable here. The Purposive Sampling method is utilised in the sampling technique. Out of 135 samples, 27 were deemed to have met the criteria. The statistical package SPSS, version 26, along with its multiple linear regression analysis tools, was used to process the data for this study. This study found that tax evasion is affected by profitability, leverage, and capital intensity all at once. Tax avoidance is affected by capital intensity and profitability to a lesser extent than by leverage.